Environmental Physiology of the Mangrove Rivulus, Kryptolebias marmoratus, A Cutaneously Breathing Fish That Survives for Weeks Out of Water - Wright, Patricia A. (Oxford University Press, 2012)
The mangrove rivulus (Kryptolebias marmoratus) is an excellent model species for understanding the physiological mechanisms that fish use in coping with extreme environmental conditions, particularly cutaneous exchange during prolonged exposure to air. Their ability to self-fertilize and produce highly homozygous lineages provides the potential for examining environmental influences on structures and related functions without the complications of genetic variation. Over the past 10 years or so, we have gained a broader understanding of the mechanisms K. marmoratus use to maintain homeostasis when out of water for days to weeks. Gaseous exchange occurs across the skin, as dramatic remodeling of the gill reduces its effective surface area for exchange. Ionoregulation and osmoregulation are maintained in air by exchanging Na(+), Cl(−), and H(2)O across skin that contains a rich population of ionocytes. Ammonia excretion occurs in part by cutaneous NH(3) volatilization facilitated by ammonia transporters on the surface of the epidermis. Finally, new evidence indicates that cutaneous angiogenesis occurs when K. marmoratus are emersed for a week, suggesting a higher rate of blood flow to surface vessels. Taken together, these and other findings demonstrate that the skin of K. marmoratus takes on all the major functions attributed to fish gills, allowing them to move between aquatic and terrestrial environments with ease. Future studies should focus on variation in response to environmental changes between homozygous lineages to identify the genetic underpinnings of physiological responses.